2022
DOI: 10.1186/s40538-022-00327-x
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the potential of co-applied biochar and plant growth-promoting rhizobacteria (PGPR) for sustainable agriculture under stress conditions

Abstract: Sustainable food security is a major challenge in today’s world, particularly in developing countries. Among many factors, environmental stressors, i.e., drought, salinity and heavy metals are major impediments in achieving sustainable food security. This calls for finding environment-friendly and cheap solutions to address these stressors. Plant growth-promoting rhizobacteria (PGPR) have long been established as an environment-friendly means to enhance agricultural productivity in normal and stressed soils an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…The biochar also increased leaf area with a rise of 26% and 36% compared with the values measured in the untreated plants. Moreover, the amendment increased twofold root length, root surface area, and root, stem, and leaf biomasses in comparison with untreated plants (Simiele et al, 2022), could have a promoting effect on plant growth as an indirect consequence of its positive effect on growth medium parameters such as water holding capacity and pH enhancement, increased nutrient availability (Malik et al, 2022). Xi et al (2020) reported that the 2% (w/w) rice biochar application increased soil available N and K, resulting in taller lettuce plants, with longer roots, stronger leaves and stems, as well as greater leaf area.…”
Section: Biochar As a Plant Growth Regulatormentioning
confidence: 99%
“…The biochar also increased leaf area with a rise of 26% and 36% compared with the values measured in the untreated plants. Moreover, the amendment increased twofold root length, root surface area, and root, stem, and leaf biomasses in comparison with untreated plants (Simiele et al, 2022), could have a promoting effect on plant growth as an indirect consequence of its positive effect on growth medium parameters such as water holding capacity and pH enhancement, increased nutrient availability (Malik et al, 2022). Xi et al (2020) reported that the 2% (w/w) rice biochar application increased soil available N and K, resulting in taller lettuce plants, with longer roots, stronger leaves and stems, as well as greater leaf area.…”
Section: Biochar As a Plant Growth Regulatormentioning
confidence: 99%
“…The maximum plant beneficial effect observed in ARN7 + GS-BC treatment can be attributed to the synergistic effects of biochar and PGPR. In general, biochar provides a stable environment for microbial growth and survival, thereby improving their colonization and subsequent PGP activity [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…By creating a favorable environment for these microorganisms, biochar indirectly supports the crop's ability to withstand stressors associated with climate change, such as pests and diseases (Bibi and Rahman 2023). Numerous studies have consistently demonstrated the bene cial impact of soil amendments, such as biochar, on promoting crop growth and enhancing crop yields through the improvement of soil and water conditions (Ullah et al 2021;Malik et al 2022;Tyagi et al 2023). These amendments work by increasing the availability of essential nutrients, enriching organic matter content, and enhancing overall soil quality (Hussain et al 2019;Ye et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The combined application of biochar and FYM in agricultural practices has emerged as a promising strategy that offers synergistic bene ts surpassing the outcomes of sole applications of either biochar or FYM (Nigussie et al 2021;Seleiman et al 2021). While biochar enhances soil structure, nutrient retention, and microbial activity due to its porous nature and high carbon content (Ullah et al 2021;Malik et al 2022;Tyagi et al 2023), FYM contributes to organic matter enrichment, nutrient supplementation, and microbial diversity (Chandra et al 2022;Ahlawat et al 2023). When these two amendments are applied together, their complementary effects create a holistic impact on the soil-plant system.…”
Section: Introductionmentioning
confidence: 99%